In situ RT-PCR Optimized for Electron Microscopy Allows Description of Subcellular Morphology of Target mRNA-Expressing Cells in the Brain - Cubas-Nuñez, Laura; Duran-Moreno, María; Castillo-Villalba, Jessica; Fuentes-Maestre, Jorge; Casanova, Bonaventura; García-Verdugo, José M.; Gil-Perotín, Sara (Frontiers in Cellular Neuroscience, 2017)
In situ RT-PCR detects and amplifies mRNA while obtaining spatial information of gene expression. When the intended use is an ultrastructural analysis of morphology, the procedure may be technically challenging and quality of tissue dramatically altered. We describe a low-damaging protocol of in situ RT-PCR combined to conventional electron microscopy that preserves fine morphology. This protocol allowed us to defining a novel population of tanycytes in the third ventricle of adult mice.